Severed Language Contacts: Two Examples from the History of English - Szymański, Leszek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The phenomenon of language contact is generally viewed as establishing or maintaining relationship by speakers of different languages. As far as the English language is concerned, especially its contemporary status, it is its global reach and influence that is discussed, as well as the influence it exerts on other languages. The present text deals with a reverse phenomenon, that is the cessation of contact, which results in a change of the linguistic situation. This is exemplified with the 16th-century English Reformation, to be more precise: the establishment of the Anglican Church, and the independence of the United States in the 18th century. With these two events, the author attempts to present how the breaking of contact influenced the further development of the linguistic situation in the external history of the English language.
Keywords: the English language; linguistic situation; external history of English; English Reformation; independence of the United States